Egg shooters - Childs, Laura (Childs, Laura. Cackleberry Club mysteries., 2020)
"A murder in the local hospital is raising everyone's temperature in the latest book in the New York Times bestselling Cackleberry Club series. Suzanne Dietz co-owner of the Cackleberry Club Café is visiting her fiancée, Dr. Sam Hazelet when a masked gunman bursts into the emergency room. He shoots two people and would probably have done more damage had Suzanne not brained him with a thermos full of chili. Still, the gunman manages to escape. Now the ladies of the Cackleberry Club are determined to find the killer before he finds them"--